THE EFFECTIVENESS OF THE USE OF SERIAL CARD MEDIA IN IMPROVING SEXUAL KNOWLEDGE AMONG PUBLIC ELEMENTARY SCHOOL 36 GUNUNG SARIK STUDENTS - Ahmad Hidayat (Faculty of Public Health, Andalas University, 2021)
The high rate of violence, abuse and sexual perversion among children in Indonesia is increasingly worrying. Sexual education has not yet been included in the academic curriculum in elementary or high schools in Indonesia. Sexual education is still thematic and conducted when meeting the right moment that is not planned. The purpose of this study is to increase knowledge about sexual problem prevention behavior for children using serial card education media. This is a quasi-experimental study to increase the sexual knowledge among respondents by using serial card as education media. Study was conducted in October 2020 to 53 students of 6th grade (11-13 years old) of SDN 36 Gunung Sarik that chosen with purposive sampling. The paired data hypothesis analysis (paired t-test) results obtained from the pre-test and post-test for students showed that sexual education using serial card media was effective in increasing students' knowledge of preventive behavior from various risks of violence, harassment, and sexual perversion.Â